1998
DOI: 10.1677/joe.0.1580351
|View full text |Cite
|
Sign up to set email alerts
|

The sodium iodide symporter gene and its regulation by cytokines found in autoimmunity

Abstract: Iodide concentration by the thyroid gland, an essential step for thyroid hormone synthesis, is mediated by the Na + /I symporter (NIS). To identify factors that may regulate this process, we have studied NIS gene expression in the Fisher rat thyroid cell line (FRTL-5) by a semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR) technique. Increasing concentrations of bovine TSH (0·1, 1, 10, 50 and 100 mU/l), with or without tumour necrosis factor-(TNF ), interferon-(IFN ) or interleukin-1 (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 32 publications
4
74
0
7
Order By: Relevance
“…INFg has a variety of effects on human thyrocytes in culture; it inhibits TSH-induced TH and Tg secretion (Nagayama et al 1987, Kung et al 1992 as well as Tg mRNA expression (Sato et al 1990), TSH-induced TPO expression ) and the TSH-and cAMPinduced upregulation of TSH receptors on the thyrocyte (Nishikawa et al 1993). IFNg also inhibits the TSH-induced increase in NIS expression in rat FTRL-5 cells resulting in diminished iodide uptake (Ajjan et al 1998). Interestingly, overexpression of IFNg in thyroid cells in a transgenic mouse leads to primary hypothyroidism mainly due to a big decrease in NIS mRNA and protein expression (Caturegli et al 2000).…”
Section: The Effect Of Cytokines On Th Synthesismentioning
confidence: 99%
“…INFg has a variety of effects on human thyrocytes in culture; it inhibits TSH-induced TH and Tg secretion (Nagayama et al 1987, Kung et al 1992 as well as Tg mRNA expression (Sato et al 1990), TSH-induced TPO expression ) and the TSH-and cAMPinduced upregulation of TSH receptors on the thyrocyte (Nishikawa et al 1993). IFNg also inhibits the TSH-induced increase in NIS expression in rat FTRL-5 cells resulting in diminished iodide uptake (Ajjan et al 1998). Interestingly, overexpression of IFNg in thyroid cells in a transgenic mouse leads to primary hypothyroidism mainly due to a big decrease in NIS mRNA and protein expression (Caturegli et al 2000).…”
Section: The Effect Of Cytokines On Th Synthesismentioning
confidence: 99%
“…The molecular characterization of the regulation of iodide transport has become possible since the cloning of the NIS gene. Indeed, in recent years, the regulation of NIS expression has been extensively studied, at both mRNA and protein levels, by using either in vivo or in vitro experimental models (Table 2) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In primary cultured human thyrocytes, TSH and forskolin upregulate NIS gene expression and NIS protein abundance, with 2.5-to 2.7-fold and 2.4-to 2.7-fold increases after 24 h and 48 h respectively (15).…”
Section: Iodide Concentration and Utilization By Thyroid Cells And Imentioning
confidence: 99%
“…There is conflicting evidence on the effect of IFN-γ on thyroidal NIS expression. Whereas [64] reported that IFN-γ had no effect on iodide accumulation or NIS mRNA levels, [71] observed that IFN-γ at a high concentration (1000 U/ml) down-regulated TSH-stimulated NIS mRNA levels. The latter results were confirmed in an in vivo study by Caturegli et al (2000) that reported a severe impairment of thyroid function and a loss of typical follicular structure combined with down-regulation of NIS expression and activity in transgenic mice expressing IFN-γ in the thyroid [73].…”
Section: Other Modulators Of Nis Functionmentioning
confidence: 95%
“…The thyroidal effects of cytokines (tumour necrosis factor alpha (TNF-α) and beta (TNF-β), interferon-γ (IFN-γ), interleukins 1-alpha (IL-1α), 1-beta (IL-1β), −6 (IL-6) and transforming growth factor-beta (TGF-β)) have been evaluated in FRTL-5 cells. and reported that TNF-α inhibited TSH-stimulated NIS mRNA expression in FRTL-5 cells [68,71]. In addition, Pekary et al (1998) reported that TNF-induced inhibition of NIS expression was mediated by the activation of sphingomyelinase, an enzyme that converts sphingomyelin to ceramide in the plasma membrane [27].…”
Section: Other Modulators Of Nis Functionmentioning
confidence: 99%